Tertiary Lymphoid Structures as Independent Predictors of Favorable Prognosis in Muscle‐Invasive Bladder Cancer - Xiaodong Teng; Zhen Chen; Yanfeng Bai; Hui Cao; Jing Zhang; Liming Xu; Kaihua Liu; Yuqian Shi; Yang Shao (Cancer Medicine)
ABSTRACT Background Tertiary lymphoid structure (TLS) has been reported to be associated with prognosis and immunotherapy in certain cancers. The objective of our study was to investigate the prognostic significance of Tertiary Lymphoid Structures (TLS) within the context of Muscle‐Invasive Bladder Cancer (MIBC), while concurrently examining the clinicopathological and molecular determinants influencing TLS formation. Methods Immunohistochemistry was used to detect the expression of TLS, CD8+ T cells, B cells, and plasma cells in 119 MIBC cases, of which 80 cases were tested by next generation sequencing (NGS) for analyzing the differences in gene alterations between TLS‐negative and TLS‐positive. Results TLS were identified in 52.1% (62/119) of the MIBC cases studied. Patients exhibiting TLS demonstrated reduced T and TNM staging and prolonged overall survival (OS) compared to those lacking TLS. Multivariate analysis showed that TLS was an independent prognostic factor. Densities of B cells, CD8+ T cells, and plasma cells in tumors were significantly correlated with TLS, but in the cases with low‐density B cells, high‐density CD8+ T cells, or high‐density plasma cells, differences in OS between the tumors with TLS and without TLS were not significant. Compared with TLS‐negative tumors, TLS‐positive tumors had a lower frequency of TP53 mutations and higher frequencies of FAT1 and CDKN1A mutations. Tumor mutational burden (TMB) was not significantly different between the two groups but was significantly associated with TLS in TP53 wild‐type tumors. Conclusions TLS emerged as an independent harbinger of favorable prognosis in MIBC, predominantly mediating antitumor responses via B cells. Moreover, TP53 mutations were identified as a potential inhibitor of TLS formation.